Do Hedge Funds Exploit Rare Disaster Concerns? - Gao, George P; Gao, Pengjie; Song, Zhaogang (Review of Financial Studies, 2018)
We find hedge funds that have higher return covariation with a disaster concern index, which we develop through out-of-the-money puts on various economic sector indices, earn significantly higher returns in the cross-section. We provide evidence that these funds’ managers are more skilled at exploiting the market’s ex ante rare disaster concerns (SEDs), which may not be associated with disaster risk. In particular, high-SED funds, on average, outperform low-SED funds by 0.96% per month, but have less exposure to disaster risk. They continue to deliver superior future performance when SEDs are estimated using the disaster concern index purged of disaster risk premiums and have leverage-managing and extreme market-timing abilities. Received June 30, 2014; editorial decision August 26, 2017 by Editor Laura Starks. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web Site next to the link to the final published paper online.